(3ceGd GdaQMI aj OaY GdSehe hMaX GdUMIs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdMdje, GdeOHQ GdMcje, Pi GdbhI hGdSdWGf, CPcQ ai ebOeJg JYQja Yde GdWH hQSeg , hCHjf hLg Seh hSeg hGSeg, eJVefkG GdbGfhf hejRGf MaX UMI HOf GdEfSGf hESJOGeI hGYJOGd eRGLg s
(3BNQgG (B:s
(3aYde SjOgG Cfg eSehe aSCdgG Yf Pdc aWdHJ efg GdCeGf hMbbJ dg GdbUI, aCMSf EdjgG hCNQLgG s
(3Vef eLehY s
(3GfXQg eY OaY GdSehe Qbe (B467s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B209 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B324 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs